EFFECT OF PLANT PHOTOSENSITIZER PSORALEN ON MITOCHONDRIAL STRUCTURES IN INFLAMMATORY PROCESSES - Nigora F. Abdukhalikova; Bakhtiyor U. Iriskulov (Central Asian Journal of Medicine, 2022)
The effects of the plant photosensitizer psoralen in various combinations on experimental chronic inflammatory conditions and its mitochondrial structures in the liver have been demonstrated in this paper. Liver mitochondrial suffocation in chronically inflamed rats was found to be 140.0 ± 6.5% higher than in healthy rats. Under conditions of chronic inflammation, high permeability pores of hepatic mitochondria were found to inhibit increased permeability of mPTP by 35.7 ± 2.5% and psoralen by 22.6 ± 1.5% compared with those of chronically inflamed rats. However, under similar conditions, it can be seen that the complex effect of UV-irradiation and psoralen reliably inhibits hepatic mitochondrial suffocation by 50.0 ± 4.5% and maintains the homeostasis of calcium ions in the matrix. Decreased ATP synthesis under the influence of various disorders in the mitochondria alters the cycle of potassium ions in the membrane. Examination of the activity of K+ ATP-channels of isolated liver mitochondria revealed the following results. Experimental chronic inflammation was found to be 21.1 ± 1.2% more active when the K+ ATP-duct permeability of their liver mitochondria was exposed to UV-irradiation than in rats with chronic inflammation. Specific administration of psoralen has been shown to increase mitoK+ ATP -channel activity by 13.1 ± 0.3% compared with rats with chronic inflammation. The complex effect of psoralen and UV-irradiation led to the activation of mitochondrial K+ ATP-channel activity by 30.2 ± 2.4% compared with those of chronically inflamed rats. From the results obtained, it can be concluded that the complex effect of psoralen and UV-radiation showed the highest effect on the structures in the mitochondrial membrane under experimental chronic inflammatory conditions.